Rheological properties of traditional balsamic vinegar: New insights and markers for objective and perceived quality - Pasquale M. Falcone; Elisa Sabatinelli; Federico Lemmetti; Paolo Giudici (International Journal of Food Studies)
The molecular structure of Traditional Balsamic Vinegar (TBV) undergoes shear-induced and timedependent jamming transitions due to the high solute concentration and self-assembling phenomena of high molecular size melanoidins with very-long relaxation times (12 years at least or more than 25). The purpose of this work was to perform a descriptive and quantitative evaluation of relationships between rheological properties, vinegar composition, and perceptual assessment of sensory properties according to the official sensory procedure. With this aim, vinegars having quality traits matching legal requirements for the PDO designation were analyzed for their reducing sugars (glucose and fructose), volatile acidity, fixed acidity, pH, Brix degree, and density as well as for their flow behaviour and dynamic viscosity over a wide range of shear rates. Results showed that flow behaviour of TBV was affected by jamming properties over wide-scale ranges of shear rate producing flow instability below a shear rate of 60 s−1 . Homogeneous, continuous flow was found at medium-high shear rates with thickening and/or thinning traits. A common onset for the structure scaling was mathematically estimated to occur close to when the density was 1.32 gmL−1 . Comparative analysis of rheological, compositional and sensory properties suggested that the colloidal jamming of the vinegar melanoidins dominated the total olfactive and gustative stimuli, and determined the classification of the vinegars that had a higher dynamic viscosity but more homogeneous flow as being of the highest commercial quality category. A robust statistical model was proposed encoding for the top-down decision-making process for quality assignment according to the official sensory procedure, using composition and flow properties as predictor variables.